Forward Electromagnetic Scattering Models for Sea Ice - Golden, K. M.; Cheney, M.; Ding, K. H.; Fung, A. K.; Grenfell, T. C.; Isaacson, D.; Kong, J. A.; Nghiem, S. V.; Sylvester, J.; Winebrenner, D. P. (2004)
Recent advances in forward modeling of the electromagnetic scattering properties of sea ice are presented. The results have direct relevance to microwave remote sensing, and serve at the basis for inverse algorithms for reconstructing the physical properties of sea ice from scattering data.